Language acquisition in Setswana speaking infants aged 8 to 18 months - Yalala, Sefela (Linguistics, 2023)
Little is known about the early acquisition of Setswana, with only a few small-scale studies of children under three-years-old. To address this gap, teams from southern Africa are adapting the MacArthur-Bates Communicative Development Inventory (CDI) for local languages. The CDI is an assessment tool completed by parents, which gauges a child's gestures and receptive and expressive vocabulary. This study aimed to adapt and pilot the first Setswana CDI for infants aged eight to 18 months living in Botswana. The original USCDI was adapted by three linguists who are mother-tongue Setswana speakers. Thereafter, we consulted 12 informants who are mother-tongue Setswana speakers, and either work with young children or are parents of young children. The tool was adjusted and piloted on 28 parents/caregivers of infants, who were recruited from two health clinics in urban and periurban areas. Results show that lexical comprehension and production correlate significantly with age. At 8.9 months, children could comprehend an average of 11.5 words and produce an average of three words. By 18 months, vocabulary had grown to an average of 183 words comprehended and 22.3 produced. Nouns made up 50% of receptive vocabulary and 57.1% of expressive vocabulary, while verbs made up 33.8% and 9.5% of receptive and expressive vocabulary respectively. The infants also produced between 10 and 62 actions and gestures, and these were significantly correlated with age. Children at 8-months-old knew an average of 17.5 actions/gestures, which increased to an average of 46.3 actions/gestures by 18 months. High exposure to another language besides Setswana had a significant negative effect on the gesture scores, and the lexical scores had a similar pattern although it was not statistically significant. The factors of gender and area did not have an effect on language scores. The results of this pilot are in line with findings from other studies, however this study highlights some key issues in adapting the CDI for southern African languages and cultures. The early receptive and expressive vocabulary of Setswana-speaking children has different word types to other languages. With further adaptations, the CDI developed for Setswana will be a reliable tool for measuring early acquisition.